• Save
Linear Rules
Upcoming SlideShare
Loading in...5
×

Like this? Share it with your network

Share

Linear Rules

  • 645 views
Uploaded on

How to find the Linear Rule for a Straight Line Graph or a Table of (x,y) values.

How to find the Linear Rule for a Straight Line Graph or a Table of (x,y) values.

  • Full Name Full Name Comment goes here.
    Are you sure you want to
    Your message goes here
    Be the first to comment
    Be the first to like this
No Downloads

Views

Total Views
645
On Slideshare
645
From Embeds
0
Number of Embeds
0

Actions

Shares
Downloads
0
Comments
0
Likes
0

Embeds 0

No embeds

Report content

Flagged as inappropriate Flag as inappropriate
Flag as inappropriate

Select your reason for flagging this presentation as inappropriate.

Cancel
    No notes for slide

Transcript

  • 1. Linear Relationship Rules Image Modified from Original at www.chiropractor.com
  • 2. Linear Relationship Rules Types of Linear Relationship Rules There are basically 3 types of Linear Rules: 1) Simple Addition or Subtraction Eg. y = x +2, y = x -5, y = x + 7, y = x -3 etc 2) Simple Multiplication or Division Eg. y = 2x, y = -5x, y = x/2, y = -x/5 etc 3) Combination Rule using y = mx + c Eg. y = 2x + 3, y = -3x + 1, y = 4x -2, y = -x + 7 etc
  • 3. Linear Relationship Rules When we are given a Table of Input and Output x and y values, we check for: 1) Simple Addition or Subtraction and if this does not work out then check for 2) Simple Multiplication or Division and if this does not work out then check for 3) Combination Rule using y = mx + c X Y -2 -1 -1 0 0 1 1 2 2 3
  • 4. When we do y – x for all of our (x,y) pairs, we get the same answer of “1” The rule is : y = x + 1 X Y Y - X -2 -1 -1 - -2 = 1 -1 0 0 - -1 = 1 0 1 1 – 0 = 1 1 2 2 – 1 = 1 2 3 3 – 2 = 1 To check for “Addition Rule”: Add an extra column and work out y-x values
  • 5. When we do y – x for all of our (x,y) pairs, we get the same answer of “0” The rule is : y = x + 0 which is y = x X Y Y – X -2 -2 -2 - -2 = 0 -1 -1 -1 - -1 = 0 0 0 0 – 0 = 0 1 1 1 – 1 = 0 2 2 2 – 2 = 0 To check for “Addition Rule”: Add an extra column and work out y-x values
  • 6. When we do y – x for all of our (x,y) pairs, we get the same answer of “-2” The rule is : y = x - 2 X Y Y - X -1 -3 -3 - -1 = -2 0 -2 -2 - 0 = -2 1 -1 -1 – 1 = -2 2 0 0 – 2 = -2 3 1 1 – 3 = -2 Same as “Addition Rule”: Add an extra column and work out y-x values
  • 7. When we do y – x for all of our (x,y) pairs, we get all Different answers. The rule is NOT Addition or Subtraction, so we now check for the Multiplication Rule. X Y Y - X -1 -3 -3 - -1 = -2 0 0 0 - 0 = 0 1 3 3 – 1 = 2 2 6 6 – 2 = 4 3 9 9 – 3 = 6 If we work out y-x values, but do not get “same answers”, then we need to move on and try the y / x “Multiplication Rule” checking routine
  • 8. When we do y / x for all of our (x,y) pairs, we get the same answers. The rule is : y = 3x X Y Y / X -1 -3 -3 / -1 = 3 0 0 0 / 0 = -- 1 3 3 / 1 = 3 2 6 6 / 2 = 3 3 9 9 / 3 = 3 We work out results by doing y / x “Multiplication Rule” checking
  • 9. When we do y / x for all of our (x,y) pairs, we get the same answer of “-2”. The rule is : y = -2x X Y Y / X -1 2 2 / -1 = -2 0 0 0 / 0 = -- 1 -2 -2 / 1 = -2 2 -4 -4 / 2 = -2 3 -6 -6 / 3 = -2 We work out results by doing y / x “Multiplication Rule” checking
  • 10. When we do y – x for all of our (x,y) pairs, we get the same answer of “0” The rule is : y = 1x which is y = x X Y Y / X -2 -2 -2 / -2 = 1 -1 -1 -1 / -1 = 1 0 0 0 / 0 = -- 1 1 1 / 1 = 1 2 2 2 / 2 = 1 Check for “Multiplication Rule”: Add extra column and work out y/x values
  • 11. When we do y – x for all of our (x,y) pairs, we get the same answer of “-2” The rule is : y = ¼ x which is: y = x / 4 X Y Y / X -4 -1 -1 / -4 = ¼ 0 0 0 / 0 = -- 4 1 1 / 1 = ¼ 8 2 2 / 2 = ¼ 12 3 3 / 3 = ¼ Same as “Multiplication Rule”: Add extra column and work out y/x values
  • 12. X Y Y – X 0 1 1 - 0 = 1 1 3 3 - 1 = 2 2 5 5 - 2 = 3 3 7 7 - 3 = 4 4 9 9 - 4 = 5 If our y-x values, and our y / x values, do not give us the same answer pattern, then we have a more complicated “Combination Rule” involved. X Y Y / X 0 1 1 / 0 = -- 1 3 3 / 1 = 3 2 5 5 / 2 = 2.5 3 7 7 / 3 = 2.3 4 9 9 / 4 = 2.2
  • 13. X Y 0 1 1 3 2 5 3 7 4 9 If our y-x values, and our y / x values, do not give us the same answer pattern, then we have a more complicated “Combination Rule” involved. Combination Rules are more complicated and involve both Multiplying and Adding to make a rule in the form: y = mx + c or y = mx - c m = slope, and c = y-intercept
  • 14. X Y 0 1 1 3 2 5 3 7 4 9 Working out a “Combination Rule” involves several working out steps Step 1) Work out Change in x and Change in y patterns. Step 2) m = Chg in y / Chg in x Step 3) Use “m” and any x,y pair to work out what “c” is. Step 4) Rule is y = mx + c after we substitute in the step 2 and 3 “m” and “c” answers
  • 15. X Y 0 1 1 3 2 5 3 7 4 9 Step 1 involves working out the Change in x and y values as shown here + 2 + 2 + 2 + 2+ 1 + 1 + 1 + 1 The Change in x-values is positive 1 each time. The Change in y-values is positive 2 each time.
  • 16. X Y 0 1 1 3 2 5 3 7 4 9 Calculate the Gradient Slope as: m = Change in Y / Change in X + 2 + 2 + 2 + 2+ 1 + 1 + 1 + 1 m = Change in Y / Change in X m = +2 / + 1 m = 2
  • 17. -3 3 5 -5 If we have a Graph instead of an x,y Values Table, then use: Gradient m = Rise/Run Gradient m = 4/2 = 2 m = 2 Rise = 4 Run = 2
  • 18. X Y 0 1 1 3 2 5 3 7 4 9 Use “m” with any x,y value to find out what the y-intercept “c” is + 2 + 2 + 2 + 2+ 1 + 1 + 1 + 1 m = 2 Choose an “easy” x,y value like 1,3 and along with m=2 and substitute into : y = mx + c 3 = (2)(1) + c So “c” must be: c = 1
  • 19. X Y 0 1 1 3 2 5 3 7 4 9 Substitute the “m” and “c” values into y = mx + c Rule Equation + 2 + 2 + 2 + 2+ 1 + 1 + 1 + 1 m = 2 c = 1 Substitute C = 1 with m=2 into : y = mx + c y = 2x + 1 The “Combination” Rule is: y = 2x + 1
  • 20. X Y 0 1 1 3 2 5 3 7 4 9 Use “m” with any x,y value to find out what the y-intercept “c” is + 2 + 2 + 2 + 2+ 1 + 1 + 1 + 1 m = 2 y = mx + c We know m=2 so y = 2x + ? Look at the Table 1,3 3 = (2)(1) + ? So Y = 2x + 1
  • 21. -3 3 5 -5 Steps are these: Find gradient “m” Put “m” into y = mx + c Write y = mx + ? Use an (x,y) point from the Line to figure out “c” Write final answer.
  • 22. -3 3 5 -5
  • 23. -3 3 5 -5 Gradient m = 4/2 = 2 y = 2 x + ? Use (x,y) = (2,6) 6 = 2 (2) + ? 6 = 4 + ? The Rule is : y = 2x + 2 Rise = 4 Run = 2
  • 24. -3 3 5 -5
  • 25. -3 3 5 -5 Rise = 2 Run = 2 Gradient m = 2/2 = 1 y = 1 x + ? Use (x,y) = (0,1) 1 = 1 (0) + ? 1 = 0 + ? The Rule is : y = 1x + 1 y = x + 1
  • 26. Blank X-Y Grid -3 3 5 -5
  • 27. http://passyworldofmathematics.com/